Behaviour of 14 109 Bearing Steel - Marian Cincala; Ludvik Kunz (Communications - Scientific letters of the University of Zilina, 2004)
Fatigue lifetime of 14 109 bearing steel in a high-cycle region in tension-compression has been studied experimentally. The aim was to determine the SN curve including fatigue limit, to perform fractographic observation and to analyze crack initiation sites, to discuss the large scatter of lifetime data, which is inherent to high strength steels, and to check the empirical area method to predict fatigue limit for this type of steel.